"Why am I so stuck?": A Collaborative/Therapeutic Assessment Case Discussion. Issue 4 (3rd July 2016) - Engelman, Diane H.; Allyn, J. B.; Crisi, Alessandro; Finn, Stephen E.; Fischer, Constance T.; Nakamura, Noriko
ABSTRACT: Assessors from 3 continents worked together on a single multimethod case study. Their goal was to hold the client at the center and forefront of their attitudes and thinking as each assessor focused on a specific measure or group of measures. The adult client requested a neuropsychological assessment and completed a full battery of cognitive measures as well as the MMPI–2, the Rorschach, and the Wartegg. A basic tenet of collaborative/therapeutic assessment holds that the client is a full partner in the assessment process; he or she is also seen as the final arbiter of the usefulness of the ideas derived. With that in mind, the client worked with the lead assessor to create 6 questions she wished answered by the assessment. Feedback and discussion occurred in a number of ways: through discussion sessions with the lead assessor that included extended inquiry; individualized letters from the other assessors, each addressing her 6 questions; a summary letter from the lead assessor; and a metaphorical, therapeutic story that stressed key findings from the assessment. Results converged powerfully, with similar findings from each assessor. The client stated that she felt heard and understood in the process, even by individuals who she had never met personally.